Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Riau, D.I Yogyakarta, Klaimantan Utara Dan Gorontalo - Wibisono, Gunawan; Chafizh Hisbulloh, Dika; Cahya Anggarakasih, Sabitya; Andrian, Jumigih; Rosyani, Perani; Permadi, Yuda (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This study discusses the number of principals and teachers by age group in the provinces of Riau, Yogyakarta, North Kulimantan, and Gorontoro in 2023/2024. The method used is a literature review with data analysis from various journal sources. The purpose of this study is to determine the age distribution of principals and teachers and their influence on the quality of education. Proposed solutions include increasing training for young teachers and mentoring programs for experienced school leaders. The results show an imbalance in age distribution that has an impact on the effectiveness of education.